Inkakuna in Paris: Modernist Liberalism in “El oro del Perú” by Aurora Cáceres - Ward, Thomas (2025)
Aurora Cáceres is a novelist, essayist and cultivator of historiography, autobiography, and so-called travel literature. Concomitantly, she was active as a feminist and suffragette. She is known mainly for her relationships with the modernist literary movement, a hemispheric trend concerned with modernity and with forming a unique Latin American literary expression. Oasis of art (¿1911?) and La ciudad del sol (1927), both examples of travel literature, reveal Cáceres’ predilection for analyzing Peruvian and European art. The focus of the present study is to consider the tension between the pride of Inkan art derived from Inca Garcilaso de la Vega’s Royal Commentaries and the modernist updating of the Eurocentric myth known as El Dorado. Here we will focus on “El oro del Perú”, a speech given at the University of Paris, the Sorbonne, later integrated into Oasis de arte, in a context with other publications such as her own book Ciudad del sol, nineteenth-century historiography, and Hispanic modernism. The contribution on Inkan art from an ideological position that favored El Dorado framed by modernist aesthetics reveals a capitalist desire. The lecture “El oro del Perú” coincides with liberal export economics, because it has the purpose of promoting an interest in the European powers to extract natural resources from countries that they consider peripheral; it also coincides with modernism because this movement’s desire for luxury and jewelry serves to support for the gold fever in El Dorado.